City - Scale Spatial Data Infrastructure for Solar Photovoltaic Energy Generation Assessment - Gowri Shankar Rao, R; K. Rayaguru, N; G.Renganathan, N; Kumar Thakur, Sunil (International Journal of Engineering and Technology, 2018)
Spatial data plays an vitalÂ role in decision-making for development of smart cities.Â As it is very evident thatÂ the development ofÂ Â smart and sustainable cityÂ mainly depends on its physical infrastructure such as intelligent transportation, smart energy, smart metering etc., This paperÂ provides an analysisÂ which aimsÂ using theÂ spatial data infrastructureÂ toolsÂ for estimation ofÂ theÂ regionÂ basedÂ solar PV potentialÂ generationÂ for a specific urban region . This analysis would afford a great insight in deciding a city scaled potential energy production and planning,Â an estimate of the geographical PV potentials for solar power generation is adopted. Â The total PV potential is evaluated forÂ a specific defined area and compared with the local electricity demand. The outcomes comprise of an initial valuation of the town's solar potential that can be used to upkeep organization decisions regarding reserves in solar systems.Â Successful implementation of SDIÂ finally depends on the political governance andÂ their framing policies.